Phytochemicals of nutraceutical importance [ - Prakash, Dhan; Sharma, Girish (CABI, 2014)
Nutraceuticals are bioactive phytochemicals that protect or promote health and occur at the intersection of food and pharmaceutical industries. The Book includes chapters dealing with biological and clinical effect, molecular level approach, quality assrance, bioavailability and metabolism of a number phytochemicals and their role to combat different diseases.